IMPROVING STUDENTS’ READING COMPREHENSION THROUGH COLLABORATIVE STRATEGY READING AT SMP NEGERI 1 SORONG - Adriana Joteni; Heriyanti Heriyanti; Yuliana Yuliana (Universitas Muhammadiyah Sorong, 2017)
ABSTRACTThis research aimed to find out whether or not the application of Collaborative Strategy Reading is effective to improve students’ reading comprehension achievement on descriptive text. It involved quantitative research method using quasi-experimental design with nonequivalent control group design. The sample taken from population of the second class of 2015-2016 academic year in SMP Negeri 1 Sorong, it was 24 students for each class. They were class VIII A and class VIII C. The data from students reading comprehension achievement wag gathered through multiple choice test given before and after doing treatment. Data analyzed through descriptive analysis using program of SPSS 20. The data has shown that the application of Collaborative Strategy is effective to improve students’ reading comprehension achievement on descriptive text. It’s seen form the result of the non-probability test used on Mann Whitney test sig. 0.00 < 0.05.